The Strategic Use and Potential Demand for an HIV Vaccine in Southern Africa - Desmond, Christopher; Greener, Robert (World Bank, Washington, DC, 2014)
HIV prevalence in Southern Africa is the highest in the world and the impact of HIV/AIDS in the region are devastating at all levels of society, including the wider economy. Government response has lagged behind the pace of the epidemic, but programs are now beginning to focus on a broad range of interventions to combat its further spread and to mitigate its impact. The authors investigate the issues around the targeting of an eventual HIV vaccine. There is at present no vaccine against HIV. Although several candidates are in the trial stage, it is not likely that a vaccine effective against the sub-type of the virus prevalent in Southern Africa will be available for 10-15 years. When it is, it may be expensive, only partially effective, and confer immunity for a limited period only. Vaccination programs will need to make the best use of the vaccine that is available and effective targeting will be essential. The authors identify potential target groups for a vaccine, and estimate how many individuals would be in need of vaccination. They develop a method for estimating how many cases of HIV infection are likely to be avoided for each vaccinated individual. The cases avoided are of two kinds: primary-the individual case that might have occurred in people who are vaccinated, and secondary-the number of people that the vaccinated individual would otherwise have caused to become infected. Both of these depend on assumptions about the efficacy and duration of vaccine protection and the extent and nature of sexual risk behavior in the population groups. The authors distinguish between the HIV cases averted per vaccination and the cases averted per 100 recruits into a vaccination program. The cases averted per 100 recruits is used to develop a priority ranking of the identified population groups for vaccination. The authors discuss the issue of ease of access to those groups and how the differential costs would affect the vaccination strategy. They conclude that an expensive vaccine should be administered to commercial sex workers first, while an inexpensive vaccine would be better administered first to general population groups, in particular, schoolchildren. The authors conclude with a discussion of current levels of public and private expenditure on HIV prevention and treatment, and the implications for an assessment of the willingness to pay for an eventual HIV vaccine.